Intermediate Algebra - Redden, John; Open Textbook Library (Open Textbook Library, 2012)
It is essential to lay a solid foundation in mathematics if a student is to be competitive in today's global market. The importance of algebra, in particular, cannot be overstated, as it is the basis of all mathematical modeling used in applications found in all disciplines. Traditionally, the study of algebra is separated into a two parts, Elementary and Intermediate Algebra. This textbook by John Redden, Intermediate Algebra, is the second part. Written in a clear and concise manner, it carefully builds on the basics learned in Elementary Algebra and introduces the more advanced topics required for further study in applications found in most disciplines. Used as a standalone textbook, Intermediate Algebra offers plenty of review as well as something new to engage the student in each chapter. Written as a blend of the traditional and graphical approaches to the subject, this textbook introduces functions early and stresses the geometry behind the algebra. While CAS independent, a standard scientific calculator will be required and further research using technology is encouraged. Intermediate Algebra is written from the ground up in an open and modular format, allowing the instructor to modify it and leverage their individual expertise as a means to maximize the student experience and success. A more modernized element, embedded video examples, are present, but the importance of practice with pencil and paper is consistently stressed. Therefore, this text respects the traditional approaches to algebra pedagogy while enhancing it with the technology available today. The importance of Algebra cannot be overstated; it is the basis for all mathematical modeling used in all disciplines. After completing a course sequence based on Elementary and Intermediate Algebra, students will be on firm footing for success in higher-level studies at the college level.
Chapter 1: Algebra Fundamentals -- Chapter 2: Graphing Functions and Inequalities -- Chapter 3: Solving Linear Systems -- Chapter 4: Polynomial and Rational Functions -- Chapter 5: Radical Functions and Equations -- Chapter 6: Solving Equations and Inequalities -- Chapter 7: Exponential and Logarithmic Functions -- Chapter 8: Conic Sections -- Chapter 9: Sequences, Series, and the Binomial Theorem
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks